Comparing the anterior middle superior alveolar nerve block and infraorbital nerve block for maxillary anterior teeth anesthesia: A randomized clinical trial. Issue 3 (May 2018) - Yadav, Anjani Kumar; Singh, Arpita; Pradhan, Leeza; Jaisani, Mehul R.; Dongol, Ashok; Acharya, Pradeep; Sagtani, Alok
Abstract: Objective: To compare the efficacy of the Anterior Middle Superior Alveolar nerve block with that of the Infra-orbital nerve block in achieving anesthesia in the anterior maxillary teeth. Study design: We recruited 62 patients who underwent vital tooth/teeth extraction under local anesthesia. We divided the patients into two groups: group A received Anterior Middle Superior Alveolar (AMSA) nerve block and group I received Infra-orbital nerve block (IONB). We assessed the Pulpal anesthesia by Pulp Tester with 0–10 digital reading, soft tissue anesthesia by pricking with periosteal elevator and injection pain using10 cm VAS (Visual Analogue Scale) score. We entered collected data in Microsoft excel 2010 and categorical variables analysed using Chi Square test and non-categorical variables analysed using Independent t (parametric) and Mann Whitney U (non-parametric) tests. Results: We achieved significantly higher pulpal anesthesia with infra-orbital nerve block for canine (p = .04) and 1st premolar (p = .02) as compared to anterior middle superior alveolar nerve block; but no significant difference was found in pulpal anesthesia for 2nd premolar, central and lateral incisors. The labial gingival anesthesia was significantly higher with infra-orbital nerve block than with anterior middle superior alveolar nerve block (p < 0.001). The VAS score in group I was 5.2 ± 2.1 (mean ± SD) and that in group A was 3.9 ± 1.3 (mean ± SD) which was statistically significant (p = .004). Conclusion: Anterior middle superior alveolar nerve block resulted in inadequate pulpal and soft tissue anesthesia but less injection pain. Infra-orbital nerve block produced higher pulpal anesthesia for 1st premolar and canine but more injection pain.